Real-World Efficacy and Safety of the Subcutaneous Implantable Cardioverter Defibrillator: Insights from the GASP Registry - Nikias Milaras; Evangelos Oikonomou; Konstantinos P. Letsas; Nikolaos Ktenopoulos; Sotirios Xydonas; Panagiotis Korantzopoulos; Georgios Leventopoulos; Panagiotis Dourvas; Stefanos Archontakis; Athena Batsouli; Panagiotis Mililis; Athanasios Saplaouras; et al. (Biomedicines, 2025)
Background: The advent of subcutaneous implantable cardioverter defibrillators (S-ICDs) marked a significant milestone in the course of cardiac rhythm devices, particularly for patients who are deemed at high risk for ventricular arrhythmias and sudden cardiac death. This extracardiac approach makes the S-ICD an especially valuable option for young patients, those with difficult venous access, or those at high risk of infection. Although the S-ICD does not provide pacing for bradycardia or heart failure, it has shown efficacy in treating ventricular arrhythmias while minimizing complications associated with transvenous systems. Methods: The purpose of this multicenter retrospective analysis was to assess the real-world efficacy and safety of the S-ICD in a heterogeneous population. Results: The GASP registry consisted of 114 patients, 68% male, aged 41 ± 15 years, with a mean LVEF of 50%. In the follow-up of 35 months, inappropriate shocks occurred in 7% while appropriate shocks occurred in 6.2%. The most common reasons for inappropriate shocks were myopotentials and atrial tachyarrhythmias. Thirty-day complication-free rates were 97.3%, with the majority of patients requiring device extraction due to infection. Over the longer term, four patients required re-intervention due to local discomfort, while one device was extracted for infection. In a multivariate analysis, complications were not significantly higher in the sicker population, such as those with diabetes, kidney disease requiring dialysis, or heart failure. Conclusions: These findings support the growing role of the S-ICD as an alternative to the TV-ICD, especially in patients without pacing indications.